Uji Efektivitas Ekstrak Rimpang Kunyit (Curcuma Domestica Val) Dalam Mempercepat Proses Penyembuhan Luka Sayat Pada Mencit (Mus Musculus) Jantan. - ningtyas, gusprita; , Riandini Aisyah, S.Si, M.Sc (2017)
Background: Rhizome turmeric (Curcuma domestica Val) empirically known to have an effect in wound healing, based on the literature, active compound of turmeric Rhizome in the mechanism of wound healing is curcumin. Previous studies showed that turmeric Rhizome has potential effect as antimicrobials, but the effect of curcumin in wound healing was not clearly elucidated. Objective: to know the effect of turmeric extracts in wound healing. Methods: this research is experimental laboratoris with post test control group design. The object of the study was 24mice (Mus musculus), 20 - 35 grams weight, and 2 - 3 months are divided into 4 groups by random sampling techniques. They were negative control (aquadest), a positive control (povidone iodine), groups treatment I (a 5% concentration of turmeric rhizome extract), and group treatment II (10% concentration of turmeric Rhizome extract). The test animals were given an incision in the back of the vertebrae, with parallel os with incision size of ± 2 cm, given treatment for 10 days, length of the wound (cm) and time (day) have been measured. Data were analyzed using analytical methods Shapiro wilk test - and one - way ANOVA followed by Post Hoc Test. Results:Turmeric rhizome extract with concentration of 5% and 10% can accelerate in mice with average time successive of ±7.16 day and ±6.16day respectively. One - way ANOVA showed a significantly difference rate in changing of injury size wound healingin four groups p = 0.000 (p < 0.05). Conclusion : The 5% and 10% concentrations of turmeric rhizome extracts have an accelerate wound healing of incision. 10% concentration of turmeric rhizome has the most effective dose in accelerate wound healing of incision.